Peran Orang Tua dalam Memotivasi Anak untuk Mengikuti Pendidikan Tahfiẓ al-Qur’an - Maulida Sari (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2021)
Memorizing the Qur'an is not an easy job. Parents need to be involved in guiding and motivating children to memorize the Qur'an at home, so that children's memorization be increases and strong. Sometimes, parents do not guide children back at home, only leave it to the teacher at school. So that children are less enthusiastic in memorizing the Qur'an. Thus the target of memorization that has been set has not been achieved. The purpose of this study is to determine the role of parents in children's memorization Qur'an education, the motivation of parents to send their children to memorization Qur'an education, and how parents motivate their children to take part in memorization Qur'an education at Integrated Islamic Elementary School Cendekia Darussalam. This type of research is qualitative research using field research methods. The research data were obtained through observation, interviews and documentation analysis techniques, then the data were analyzed using descriptive methods. The results obtained indicate that in the process of memorization Qur'an education for children, parents can act as mentors, managers, motivators and facilitators for children. The motivation of parents to send their children to memorization Qur'an education is so that children become memorizers of the Qur'an, parents get a crown in the hereafter, children who memorize Qur'an can be intermediary for parents to get a crown in Heaven, and add religious knowledge for children and parents. The way parents motivate their children to take part in memorization Qur'an education at Integrated Islamic Elementary School Cendekia Darussalam is to give praise, give gifts, give punishments, and tell stories, and call on children to love Allah and the Prophet. Based on the results of the study, it can be concluded that if parents do their roles well, children will be encourage, move and direct to memorize the Qur'an, so that learning destination are achieved.